Thin Layer Membrane Systems as Rapid Development Tool for Potentiometric Solid Contact Ion‐selective Electrodes. Issue 4 (8th January 2020) - Forrest, Tara; Zdrachek, Elena; Bakker, Eric
Abstract: The use of thin membrane layer ion‐selective electrodes (of ∼200 nm thickness) as rapid diagnosis tool is proposed. While conventional solid contact systems (with a membrane of ∼250 μm thickness) may exhibit a satisfactory stability for regular laboratory use, a signal degradation can still be distinguished over a longer period of time but this requires tedious and time consuming tests. By diminishing the thickness of the membrane by a factor of 10 3 approximately, diffusion processes happen faster, and the lifetime is significantly reduced. This would ordinarily be a strong drawback but not if the aim is to detect a membrane deterioration in a shorter time frame. This characteristic makes thin membrane systems an ideal tool for rapid complications identification in the development process of conventional solid contact electrodes. The approach is demonstrated here in the development of an all new solid contact probe for anions. PEDOT−C14, a conducting polymer, was used for the first time in a solid contact electrode with an anion exchange membrane for the detection of nitrate. The thin layer configuration was used to optimise the polymerisation parameters as well as the membrane composition without having to run week‐long trials. A stable conventional solid contact electrode was in the end successfully developed and exhibited a lower detection limit of 10 −5.5  M for nitrate with a stable Nernstian response for several days. Abstract :